LYRICAL EXPRESSION OF LOVE TOWARDS THE HOMELAND (Scientific journal of the Fergana State University, 2025)
The article analyzes the events and emotions reflected in the lyrics of the great German poet Heinrich Heine, based on the material of Uzbek translations of his works.